KARAKTERISTIK ERITROSIT PADA PASIEN ANAK DENGAN INFEKSI VIRUS DENGUE DI MANADO - Kewo, Indah R. A.; Rambert, Glady; Manoppo, Firginia (Universitas Sam Ratulangi, 2015)
Abstract: Dengue infection is a kind of viral infectious disease that can cause death. There are several hematological abnormalities frequently found in dengue infection, as follows: leukopenia, thrombocytopenia, coagulation disorders, bone marrow suppression, as well as increases in hemoglobin level and hematocrit value due to leakage of plasma. This study aimed to obtain the characteristic features of erythrocytes in children infected with dengue virus in Manado. This study used a cross sectional design and was conducted from December 2014 until January 2015 at Pancaran Kasih GMIM Hospital, Wolter Monginsidi Hospital, and Advent Hospital in Manado. Examination of the characteristics of erythrocytes was conducted at Prokita Malalayang Laboratory. Samples were 37 patients. The results showed that low erythrocyte count was found in 2 patients (5.41%); normal erythrocyte count in 34 patients (91.9%); and increased erythrocyte count in 1 patient (2.7%). Low mean copuscular volume (MCV) (MCHC) was found in 35 patients (94.6%), and increased MCHC in 2 patients (5.4%). Conclusion: Most children with dengue viral infection in Manado had normal erythrocyte count, along with MCV and MCHC in the range of the reference values (normocytic and normochromic).Keywords: Dengue virus infection, the number of erythrocytes, MCV, MCHC.Abstrak: Infeksi virus dengue merupakan penyakit infeksi yang dapat menyebabkan kematian. Kelainan hematologi sering muncul pada demam berdarah dengue diantaranya leukopenia, trombositopenia, gangguan koagulasi, penekanan sumsum tulang, juga terjadi peningkatan kadar hemoglobin dan nilai hematokrit karena kebocoran plasma yang dapat menyebabkan kematian. Penelitian ini bertujuan untuk mengetahui karakteristik eritrosit pada anak yang terinfeksi virus dengue di Manado. Desain penelitian potong lintang dengan jumlah sampel 37 pasien. Penelitian ini dilaksanakan di RSU Pancaran Kasih GMIM Manado, RS Wolter Mongisidi Manado, dan RS Advent Manado pada bulan Desember 2014 sampai Januari 2015. Pemeriksaan karakteristik eritrosit dilakukan di Laboratorium Prokita Malalayang. Hasil penelitian memperlihatkan jumlah eritrosit rendah ditemukan pada 2 orang (5,41%); normal 34 orang (91,9%); dan meningkat 1 orang (2,7%). Nilai mean copuscular volume (MCV) rendah pada 8 orang (21,6%); normal 28 orang (75,7%); dan meningkat 1 orang (2,7%). Nilai mean copuscular hemoglobin consentration (MCHC) normal pada 35 orang (94,6%), dan meningkat 2 orang (5,4%). Simpulan: Pada sebagian besar pasien anak dengan infeksi virus dengue di Manado didapatkan jumlah eritrosit dalam batas nilai normal, serta nilai MCV dan MCHC berada diantara rentang nilai rujukan (normositik dan normokromik).Kata kunci: infeksi virus dengue, eritrosit, MCV, MCHC